The Influence of Products and Promotional Mix on Tourists’ Decision: (Case Study of Pramuka Bee Park, Cibubur, East Jakarta) - Gagih Pradini; Bagus Syarifuddin; Kumba Digdowiseiso; Octavia Miranti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Pramuka Bee Park is one of the tourist destinations in Cibubur, East Jakarta. Our research aims to find out whether the product and promotional mix affect the decision of tourists to visit. We used a quantitative-descriptive, using primary data of questionnaires as many as 100 respondents. The data can be analyzed through multiple linear correlation analysis, instrument tests, modern feasibility tests, and T tests. This study showed that both product and promotional mix had a positive and significant effect on visiting decision.